Johns Hopkins evidence-based practice for nurses and healthcare professionals : model and guidelines - Dang, Deborah; Dearholt, Sandra; Bissett, Kim; Ascenzi, Judy; Whalen, Madeleine (Indianapolis, IN : Sigma Theta Tau International, 2022)
Building on the strength of previous versions, the fourth edition of this foundational text is fully revised to include updated content based on more than a decade of the model's use, refinement in real-life settings, and feedback from nurses and other healthcare professionals around the world.
Evidence-based practice : context, concerns, and challenges -- Creating a supportive EBP environment -- The Johns Hopkins evidence-based practice (JHEBP) model for nurses and healthcare professionals (HCPs) process overview -- The practice question phase -- Searching for evidence -- Evidence appraisal : research -- Evidence appraisal : nonresearch -- Translation -- Dissemination -- Exemplars -- Lessons from practice : using the JHEBP tools -- Appendices. A. PET Process guide ; B. Question development tool ; C. Stakeholder analysis and communication tool ; D. Hierarchy of evidence guide ; E. Research evidence appraisal tool ; F. Nonresearch evidence appraisal tool ; G. Individual evidence summary tool ; H. Synthesis and recommendations tool ; I. Translation and action planning tool ; J. Publication guide.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on August 05, 2021).
WorldCat record variable field(s) change: 610
Keywords: Johns Hopkins University. -- School of Nursing; Evidence-based nursing; Nursing models; Evidence-based nursing; Nursing models; Evidence-Based Nursing; Electronic books